Virtual Reality in Clinical Psychology - Riva, Giuseppe (Comprehensive Clinical Psychology, 2022)
From a technological viewpoint, virtual reality (VR) is a set of fancy technologies: a helmet, trackers, and a 3D visualizing system. However, from a psychological viewpoint, VR is simultaneously a simulative, a cognitive, and an embodied technology. These features make VR the perfect tool for experiential assessment and learning with great clinical potential. This potential is already supported by clinical outcomes. Two recent meta-reviews assessing more than 53 systematic reviews and meta-analyses support its use in anxiety disorders, pain management, and eating and weight disorders, with long-term effects that generalize to the real world. Recent studies have also provided preliminary support for the use of VR in the assessment and treatment of psychosis, addictions, and autism.